Implementation Of Sharia-Compliance In Islamic Bank Product Innovations - Nugroho, Eko Rial (Prophetic Law Review, 2021)
The establishment of sharia-compliant financial institutions is an effort by Muslims to live all aspects of their economic life based on the Qur'an and Hadith, and the community's need for interest-free banking. However, the development of Islamic banks around the world and in Indonesia still encounters many obstacles as they emerged amidst of the deep-rooted developments and practices of conventional banking. The success of Islamic banking is the success of implementing Islamic rules in muamalat. Nonetheless, there are still problems in their implementation. Public still doubts Islamic banks are truly Sharia-compliant. Some of the customers of Islamic banks close their accounts because they doubt the consistency of the application of Islamic principles. This is normative legal research in which the results show that Islamic banks without Islamic ethics will be trapped in an unethical Islamic business. The customers are concerned if its operational activities are mere replacement of banking terms. Additionally if it is difficult for the Islamic banks to impose sanctions to their customers as they are interest-free. There is also lack of human resources which comprehensively understand the operational systems of both conventional and Islamic banking. The implementation of a profit-sharing system requires complex calculations, particularly in the small profits shared with the customers and the not-fixed amount of savings. Although Islamic banks are oriented towards lower-income communities, there is a tendency that those who successfully get bona fide projects and credit facilities from Islamic banks are the upper class.Keywords: Sharia Compliance; Islamic Banking; Islamic EthicsImplementasi Kepatuhan Syariah dalam Inovasi Produk Perbankan SyariatAbstrakPendirian lembaga keuangan syariah merupakan sebuah upaya dari umat Islam untuk menjalani seluruh aspek kehidupan ekonominya berdasarkan Al-Qur'an dan Hadist, serta kebutuhan masyarakat akan perbankan yang bebas bunga. Namun, perkembangan perbankan syariah di seluruh dunia dan di Indonesia masih menghadapi banyak kendala karena muncul di tengah-tengah perkembangan dan praktik perbankan konvensional yang mengakar. Keberhasilan perbankan syariah adalah penerapan aturan syariah dalam muamalat. Meskipun demikian, masih terdapat kendala-kendala dalam pelaksanaannya. Masyarakat masih meragukan perbankan syariah benar-benar berbasis syariat. Sebagian nasabah bank syariah menutup rekeningnya karena meragukan konsistensi penerapan prinsip syariat. Ini merupakan penelitian hukum normatif yang hasilnya menunjukkan bahwa perbankan syariah tanpa etika syariah akan terjebak dalam bisnis syariah yang tidak etis. Nasabah khawatir jika kegiatan operasional dari perbankan syariah hanya mengganti istilah perbankan konvensional, apalagi jika perbankan syariah sulit menerapkan sanksi kepada nasabahnya karena nasabah tidak dikenakan bunga. Sumber daya manusia yang memahami sistem operasional perbankan secara komprehensif masih kurang, baik konvensional maupun syariah. Penerapan sistem bagi hasil pun membutuhkan perhitungan yang rumit, terutama dalam kecilnya keuntungan yang dibagikan kepada nasabah dan jumlah tabungan yang tidak tetap. Meskipun perbankan syariah berorientasi pada masyarakat berpenghasilan rendah, namun terdapat kecenderungan bahwa yang berhasil mendapatkan proyek dan fasilitas kredit yang menguntungkan dari perbank syariah adalah kalangan atas.Kata Kunci: Kepatuhan Syariah; Perbankan Syariah; Etika Islami